Power of gentleness : meditations on the risk of living - Dufourmantelle, Anne (Fordham University Press, 2018)
The simplicityof gentleness is misleading. It is an active passivity that may become anextraordinary force of symbolic resistance and, as such, become central to bothethics and politics. Gentleness is a force of secret life-giving transformationlinked to what the ancients called potentiality. Gentleness is a power.